WATER USE EFFICIENCY AND PEPPER YIELD UNDER DIFFERENT IRRIGATION AND FERTILIZATION REGIME - Tanaskovik, Vjekoslav; Cukaliev, Ordan; Romić, Davor; Ondrasek, Gabrijel; Savić, Radovan; Markoski, Mile; Nechkovski, Stojanche (Macedonian Academy of Sciences and Arts, 2019)
The primary objective of this study was to determine water use efficiency (WUE) and pepper yield under differ-ent irrigation and fertilization regimes. For this purpose, a three-year field experiment was conducted with pepper, grown in a plastic house in the Skopje region. Four experimental treatments were applied in this study. Three of the treatments were drip fertigated (DF1, DF2, DF3), while the last one was furrow irrigated with conventional application of fertilizer (ØB). The results obtained clearly showed that treatments DF1, DF2, and DF3 resulted in significantly higher marketable and dry pepper yield in comparison to treatment ØB. Also, drip fertigation frequency at four and two days (DF2 and DF1) resulted in 9.6 % to 13.6 % higher marketable and 17.6 % to 20.1 % dry pepper yield when compared with drip fertigation scheduled by tensiometers (DF3). Also, our results indicate that drip fertigation is an effective prac-tice in achieving significantly higher WUE. Namely, WUE was 2.50, 2.47, 1.99 and 1.54 kg/m3 for the treatments DF1, DF2, DF3 and ØB, respectively.